On the natural convection heat transfer in the casing annulus of oil wells - Shoushtari, M.A. (2011)
Radial heat transfer between the inner pipe fluid flow and the formation surrounding the oil wells occurs by overcoming various resistances in series. The major resistance is within the annular space between the wellbore tubing and the casing; and it is crucial to estimate the convection heat transfer coefficient in this apace. The present work aims to investigate the nature, and predict the natural convection heat transfer coefficient in the annulus, which is hard to predict due to the large length-to-spacing ratio (aspect ratio). The approach to model the natural convection heat transfer in this work is by analytical and numerical techniques. The annular space between the tubing and the casing was treated as a finite space bounded by walls and filled with fluid media (enclosures). Correlations for vertical enclosures were employed in the study. The flow field of such a case was modeled and simulated for numerical analysis, using ANSYS-FLUENT – 12 software package. Some boundary parameters have been defined by the user and fed to the software. The predicted values of Nusselt numbers from both, analytical and numerical were compared with those of previous experimental investigations. Keywords: Annular natural convection, Casing annulus, Numerical analysis, Oil wells.